2014
DOI: 10.1021/ml400527n
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Benzomorpholine Class of Diacylglycerol Acyltransferase I Inhibitors

Abstract: Diacylglycerol acyltransferase 1 (DGAT1) presents itself as a potential therapeutic target for obesity and diabetes for its important role in triglyceride biosynthesis. Herein we report the rational design of a novel class of DGAT1 inhibitors featuring a benzomorpholine core (23n). SAR exploration yielded compounds with good potency and selectivity as well as reasonable physical and pharmacokinetic properties. This class of DGAT1 inhibitors was tested in rodent models to evaluate DGAT1 inhibition as a novel ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The information provided by this study on synthetic peptide corresponding to substrate binding sites should therefore contribute to understanding of the functioning of theses enzymes in metabolic disorders [33], and the development of novel inhibitors [34]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information provided by this study on synthetic peptide corresponding to substrate binding sites should therefore contribute to understanding of the functioning of theses enzymes in metabolic disorders [33], and the development of novel inhibitors [34]. …”
Section: Discussionmentioning
confidence: 99%
“…Given the DGAT1 enzymes represent interesting therapeutic targets in obesity [ 5 – 7 ], insulin resistance [ 10 , 31 ], and in hepatitis C virus infection [ 32 ], it is important that DGAT1 structure-activity relationships are characterized, especially in the absence of any crystal structure of this enzyme or a close homologue. The information provided by this study on synthetic peptide corresponding to substrate binding sites should therefore contribute to understanding of the functioning of theses enzymes in metabolic disorders [ 33 ], and the development of novel inhibitors [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, we studied some 3(2H)-pyridazinone compounds [2][3][4][5]. In this content, as a continuation of our spectroscopic and quantum chemical calculation studies on the mentioned pyridazinones, we found that the 4-ethoxy-2-methyl-5-(4-morpholinyl)-3(2H)-pyridazinone isalso to be worth to investigate by using the FT-IR and UV-vis spectroscopies and quantum chemical calculations [6][7][8][9][10][11][12]. However, the spectral and theoretical studies on this compound used as an analgesic and anti-inflammotory drug in the pharmacologywere not taken place in the literatureto our best knowledge.…”
mentioning
confidence: 94%
“…However, the spectral and theoretical studies on this compound used as an analgesic and anti-inflammotory drug in the pharmacologywere not taken place in the literatureto our best knowledge. The 4-ethoxy-2-methyl-5-(4-morpholinyl)-3(2H)-pyridazinone compound has two scaffold six-membered rings called pyridazinone and morpholinewhich is considered an important building block in the medicine chemistry field [11,12]. However, the pyridazinone ring has two adjacent nitrogen atoms at 1 and 2 positions in a six-membred ring and a carbonyl group at 3 position while the morpholine block possess one nitrogen and an oxygen atoms in the ring [13,14].…”
mentioning
confidence: 99%
“…We have evaluated the 2(1 H )‐pyrazinone as a P 3 core structure in the development of new inhibitors of the HCV NS3 protease and drug‐resistant variants,8 and we eventually discovered that a tert ‐butylurea functionality in the 3‐position of the 2(1 H )‐pyrazinone resulted in an increased inhibition of the HCV NS3 protease (e.g., I , Figure 1). 7c…”
Section: Introductionmentioning
confidence: 99%